Engineering, Procurement and Construction of Railway Projects Model Agreement - Planning Commission (Planning Commission, 2014)
Construction works in the public sector including the Railways are primarily undertaken through the conventional ‘item rate’ contracts. The ‘item-rate’ contracts, however, tend to suffer from significant time and cost overruns and have, therefore, resulted in huge delays and cost overruns in bulk of the public sector construction projects. These contracts also lead to malfeasance and disputes in view of the vast discretion to alter the quantities of work during the construction process. In view of the above, the Committee on Infrastructure, under the chairmanship of Prime Minister, had decided that the ‘item rate’ contracts for highway projects may be substituted with the Engineering, Procurement and Construction (EPC) contracts, which provide certainty of price as well as time in completion of such projects.
Planning Commission Government of India
Planning Commission Government of India